Proceedings of the Thirtieth Annual Symposium on Computational Geometry 2014
DOI: 10.1145/2582112.2582143
|View full text |Cite
|
Sign up to set email alerts
|

New and Improved Spanning Ratios for Yao Graphs

Abstract: For a set of points in the plane and a fixed integer k > 0, the Yao graph Y k partitions the space around each point into k equiangular cones of angle θ = 2π/k, and connects each point to a nearest neighbor in each cone. It is known for all Yao graphs, with the sole exception of Y5, whether or not they are geometric spanners. In this paper we close this gap by showing that for odd k ≥ 5, the spanning ratio of Y k is at most 1/(1 − 2 sin(3θ/8)), which gives the first constant upper bound for Y5, and is an impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 16 publications
2
45
0
Order By: Relevance
“…Is the tradeoff between stretch 1 + and n · O( −d+1 ) edges tight?We remark that the Θ-graph and its variants provide stretch 1 + only for sufficiently small angle Θ. These graphs have also been studied for fixed values of Θ; see [10,6,11,5,40,37,9], and the references therein. The general goal here is to determine the best possible stretch for small values of Θ.…”
mentioning
confidence: 99%
“…Is the tradeoff between stretch 1 + and n · O( −d+1 ) edges tight?We remark that the Θ-graph and its variants provide stretch 1 + only for sufficiently small angle Θ. These graphs have also been studied for fixed values of Θ; see [10,6,11,5,40,37,9], and the references therein. The general goal here is to determine the best possible stretch for small values of Θ.…”
mentioning
confidence: 99%
“…Graph Stretch Factor [6] Y2, Y3 ∞ [5] Y4 8 √ 2(26 + 23 √ 2) 662.16 [1] Y5 2 + √ 3 3.74 [1] Y6 5.8 [4] Y k , k ≥ 7 (1 + √ 2 − 2 cos θ)/(2 cos θ − 1), where θ = 2π/k [3] Y Our contributions. We show that the stretch factor of Y 4 is at most (11 + 7 √ 2) 4 + 2 √ 2 54.62, which is a significant improvement upon the best previously known upper bound of 662.16 from [5].…”
Section: Referencementioning
confidence: 99%
“…In each sector, n selects the closest node and connects to it with a directed edge. It has been shown that the Yao graph is a spanner for k ≥ 4 [3]. The Yao-Yao graph builds on top of the Yao graph.…”
Section: ) Implementation Issuesmentioning
confidence: 99%